Meningkatkan Kreativitas Siswa Dalam Pembelajaran Muatan IPAS Menggunakan Model READING Di Kelas IV SDN Banua Anyar 4 Banjarmasin - Muetia Patmah; Novitawati (CV. ITTC INDONESIA, 2025)
The problem in this study is the low creativity of students in learning. Students' difficulty in understanding the material presented by the teacher is one of the factors that causes this. In addition, the learning resources in the lesson are still incomplete, so to complete the material, it is necessary to search one by one for each part. These two factors result in low levels of student creativity. This problem can be overcome by implementing the READING combination learning model. This study aims to explain the activities of teachers and students, analyze the increase in creativity and student learning outcomes. This study is a type of Classroom Action Research which is carried out with 4 meetings. The subjects of this study were 12 fourth grade students of SDN Banua Anyar 4 Banjarmasin. This research was conducted in semester 2, academic year 2023/2024. This study uses a qualitative approach. The data presented in this study are qualitative data obtained from observations of teacher and student activities, as well as student creativity. Quantitative data in this study were obtained from student learning outcomes. The results of this study stated that teacher activity at the first meeting scored 18, the second meeting scored 20, the third meeting scored 25 and the fourth meeting scored 27. The percentage of children's activity at the first meeting was 50%, the second meeting 58%, the third meeting 68%, and the fourth meeting 83%. Percentage of children's creativity in first meeting was 25%, the second 50%, the third 75%, and the fourth 100%. This has an impact on student learning outcomes, at the first meeting, student learning outcomes got a percentage of 58%, the second 58%, the third 75%, and the fourth 92%. The conclusion is learning with READING model can increase teacher and student activity, as well as student creativity and lear